2021
DOI: 10.1073/pnas.2112942118
|View full text |Cite
|
Sign up to set email alerts
|

A serum-stable RNA aptamer specific for SARS-CoV-2 neutralizes viral entry

Abstract: The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic has created an urgent need for new technologies to treat COVID-19. Here we report a 2′-fluoro protected RNA aptamer that binds with high affinity to the receptor binding domain (RBD) of SARS-CoV-2 spike protein, thereby preventing its interaction with the host receptor ACE2. A trimerized version of the RNA aptamer matching the three RBDs in each spike complex enhances binding affinity down to the low picomolar range. Binding mode and spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
109
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(111 citation statements)
references
References 61 publications
2
109
0
Order By: Relevance
“… 10 A trimeric RNA aptamer was shown to neutralize wild-type SARS-CoV-2 entry to cells. 28 Therefore, designed SCORe.50 dimers that connect two SCORe.50 with a 12-, 20-, or 30-nt stretch of A–T complementary binding to augment binding affinity for Omicron RBD ( Figure S7A ). We first show costaining between fluorescently labeled SCORe.50 and BA.1 RBD binding to ACE2-overexpressing cells ( Figure S7B ).…”
Section: Resultsmentioning
confidence: 99%
“… 10 A trimeric RNA aptamer was shown to neutralize wild-type SARS-CoV-2 entry to cells. 28 Therefore, designed SCORe.50 dimers that connect two SCORe.50 with a 12-, 20-, or 30-nt stretch of A–T complementary binding to augment binding affinity for Omicron RBD ( Figure S7A ). We first show costaining between fluorescently labeled SCORe.50 and BA.1 RBD binding to ACE2-overexpressing cells ( Figure S7B ).…”
Section: Resultsmentioning
confidence: 99%
“…The screening procedures of structure similarity, docking, and MD simulations can be applied to perform the in-silico selection of aptamers for screening a large number of mutated sequences. The computational results obtained from our study reveal that the RBD-1CM1 aptamer can have strong interactions with the RBD of the S1 subunit, which also has the potential for diagnosis applications, such as in rapid test kits [ 12 ] and aptamer-based biosensors [ 11 ], or for the treatment of SARS-CoV-2 [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Sun, Liu, Song, et al ( 2021 ) demonstrated that aptamer cocktails displayed the higher RBD and pseudovirus neutralizing efficiency compared to their individual aptamer counterparts with the same concentration. In terms of aptamer multimerization, Valero et al ( 2021 ) engineered dimeric and trimeric versions of RBD‐PB6‐Ta aptamers via a scaffolding or poly(A) linkage approach. Compared to the monomeric aptamer, both dimeric and trimeric forms demonstrated an enhanced spike protein binding avidity ( K D values of 0.4 nM, 72 pM, and 39 pM for monomer, dimer, and trimer, respectively) and efficiently neutralized real SARS‐COV‐2 virus with respective IC 50 values of 1.5 μM, 387 nM, and 46 nM.…”
Section: Coronavirus Aptamer Selection Category and Engineeringmentioning
confidence: 99%